Recurrent genomic alterations in sequential progressive leukoplakia and oral cancer: drivers of oral tumorigenesis? - Cervigne, Nilva K.; Machado, Jerry; Goswami, Rashmi S.; Sadikovic, Bekim; Bradley, Grace; Perez-Ordonez, Bayardo; Naranjo Galloni, Natalie; Gilbert, Ralph; Gullane, Patrick; Irish, Jonathan C.; Jurisica, Igor; Reis, Patricia Pintor dos [UNESP]; et al. (Oxford University Press, 2014)
A significant proportion (up to 62) of oral squamous cell carcinomas (OSCCs) may arise from oral potential malignant lesions (OPMLs), such as leukoplakia. Patient outcomes may thus be improved through detection of lesions at a risk for malignant transformation, by identifying and categorizing genetic changes in sequential, progressive OPMLs. We conducted array comparative genomic hybridization analysis of 25 sequential, progressive OPMLs and same-site OSCCs from five patients. Recurrent DNA copy number gains were identified on 1p in 20/25 cases (80) with minimal, high-level amplification regions on 1p35 and 1p36. Other regions of gains were frequently observed: 11q13.4 (68), 9q34.13 (64), 21q22.3 (60), 6p21 and 6q25 (56) and 10q24, 19q13.2, 22q12, 5q31.2, 7p13, 10q24 and 14q22 (48). DNA losses were observed in 20 of samples and mainly detected on 5q31.2 (35), 16p13.2 (30), 9q33.1 and 9q33.29 (25) and 17q11.2, 3p26.2, 18q21.1, 4q34.1 and 8p23.2 (20). Such copy number alterations (CNAs) were mapped in all grades of dysplasia that progressed, and their corresponding OSCCs, in 70 of patients, indicating that these CNAs may be associated with disease progression. Amplified genes mapping within recurrent CNAs (KHDRBS1, PARP1, RAB1A, HBEGF, PAIP2, BTBD7) were selected for validation, by quantitative real-time PCR, in an independent set of 32 progressive leukoplakia, 32 OSSCs and 21 non-progressive leukoplakia samples. Amplification of BTBD7, KHDRBS1, PARP1 and RAB1A was exclusively detected in progressive leukoplakia and corresponding OSCC. BTBD7, KHDRBS1, PARP1 and RAB1A may be associated with OSCC progression. Proteinprotein interaction networks were created to identify possible pathways associated with OSCC progression.